SLC6A4 promoter region methylation and socio-emotional stress response in very preterm and full-term infants. (July 2016) - Montirosso, Rosario; Provenzi, Livio; Giorda, Roberto; Fumagalli, Monica; Morandi, Francesco; Sirgiovanni, Ida; Pozzoli, Uberto; Grunau, Ruth; Oberlander, Tim F; Mosca, Fabio; Borgatti, Renato
Aim: The present study is part of a prospective micro-longitudinal research project and reports on the association between SLC6A4 methylation and socio-emotional stress response in very preterm (VPT) and full-term (FT) infants.Materials & methods: SLC6A4 methylation was assessed at birth and discharge in 32 VPT infants, and at birth in 27 FT infants. Socio-emotional stress response (i.e., negative emotionality) was assessed at 3 months (corrected age).Results: Negative emotionality was higher in VPTs compared with FT counterpart. In VPT infants only, stress response was associated with SLC6A4 methylation status at discharge, which was predictive of greater negative emotionality.Conclusion: The present study extends previous reports, suggesting that altered SLC6A4 methylation associates with greater socio-emotional stress sensitivity in 3-month-old VPT infants.